2014
DOI: 10.1177/0193945914529025
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Utilizing Ethnic Beauty Salons for Cervical Cancer Screening Education

Abstract: The purpose of this study was to assess the feasibility of using ethnic beauty salons to reach out to Vietnamese and Korean American women for cervical cancer screening education. Participants (N = 62) were conveniently recruited from ethnic beauty salons located in Albuquerque, NM. Two feasibility questionnaires were separately administered to cosmetologists and their customers. Findings support the view that ethnic beauty salons can be used as a gateway to reach out to these populations, and cosmetologists h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 21 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…Both cosmetologists and customers expressed comfort with cervical cancer education in the beauty salon setting (72.2% and 88.6%, respectively). 20 Aside from cancer, chronic disease prevention was the focus of three studies. Kleindorfer et al 21 used a pre/ postintervention design to educate African American women on stroke risk factors and warning signs in Cincinnati, OH, USA, and Atlanta, GA, USA.…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Both cosmetologists and customers expressed comfort with cervical cancer education in the beauty salon setting (72.2% and 88.6%, respectively). 20 Aside from cancer, chronic disease prevention was the focus of three studies. Kleindorfer et al 21 used a pre/ postintervention design to educate African American women on stroke risk factors and warning signs in Cincinnati, OH, USA, and Atlanta, GA, USA.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studies reviewed also indicate that diverse ethnic/racial cosmetologists had an interest in health 10,11,20 and were comfortable or very comfortable in talking about health topics. 20,25 Two studies reported that cosmetologists improved their knowledge levels, including knowledge about skin cancer 24 and knowledge about stroke risk factors and warning signs. 21 Studies indicated that cosmetologists were interested in learning more about health with one noting that they preferred to use flexible ways to learn on their own time (reading pamphlets and watching videos).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…4,5 The literature review shows that cosmetologists undertake talks with their patients on the topics related to health and illness. 6,7 Moreover beauty salons are indicated by many authors as suitable places for increasing the awareness and educating patients about positive health behaviors [7][8][9][10][11][12][13] (Table 1).…”
Section: Introductionmentioning
confidence: 99%